The Effects of SME Performance on Credit Accessibility in Border Economic Zones: The Case of Nong Khai Province, Thailand - Rangsungnoen, Grid (Journal of Business, Innovation and Sustainability (JBIS), 2023)
This study examines and models how firm competitiveness, managing uncertainty, and government support affect the performance of small and medium-sized enterprises (SME), focusing on impacts of credit accessibility for SMEs in border areas. Quantitative design underpinned by performance theory support analysis of 362 valid survey responses obtained in Nong Khai, Thailand, during November – December 2020. Confirmatory factor analysis (CFA) and structural equation modelling (SEM) demonstrate the structural relationships among the proposed constructs. Findings indicate that there was a significant positive relationship between firm performance and credit accessibility. Therefore, enhancing SME performance by increasing firm competitiveness, managing uncertainty, and government support would improve financial acquisition outcomes. Studying SMEs in Nong Khai's vital border economic zone provides valuable insights to maximize international gateway trade and to other regions with similar characteristics highlighting how three significant direct drivers can improve the performance of SMEs thus enhancing their credit accessibility.